Determinación del hipotiroidismo subclínico como causa de infertilidad. - Acosta Bastidas, Dayana Carolina (2023)
ABSTRAC Subclinical Hypothyroidism is defined by increased thyroid-stimulating hormone (TSH) levels, while free thyroxine (FT4) levels remain within normal limits. Infertility refers to the inability to achieve a pregnancy after at least 12 months of sexual intercourse without using contraception. Subclinical hypothyroidism affects fertility in women and men. It can cause problems in the hormonal axis, irregular menstrual cycle, reduced semen quality and a low success rate in fertility treatments. In Ecuador, subclinical hypothyroidism is a common medical condition in the adult population, with a prevalence of 8.6%. Levothyroxine sodium treatment may improve thyroid function and potentially benefit fertility in both sexes. Objective: the objective of the research is to determine subclinical hypothyroidism as a cause of infertility. Methods: A descriptive level investigation, non-experimental design, cross-sectional sequence and retrospective chronology, was carried out through scientific platforms such as Pubmed, UpToDate, Scopus, Google Scholar, Cochrane, Scielo, Redalyc and Medline in a period of 2018. to 2023; aimed at the study of subclinical hypothyroidism as a cause of infertility, clinical and epidemiological characteristics, the elements that allow the diagnosis of the disease and the therapeutic schemes used in its treatment, as well as the mechanisms by which subclinical hypothyroidism can be considered as a cause of infertility. Results: The relationship between subclinical hypothyroidism and infertility problems was obtained through bibliographical reviews of studies carried out. Conclusion: The bibliographic review shows a connection between subclinical hypothyroidism and infertility. Studies reveal that there is a higher prevalence of this condition in women than in men. Therefore, it is advisable to perform thyroid tests to detect or diagnose this problem in time and prevent complications that may affect the reproductive quality of patients. Keywords: Subclinical hypothyroidism, infertility, thyroid, thyrotropin